2012
DOI: 10.1007/s12033-012-9628-2
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of StDREB1 Transcription Factor Increases Tolerance to Salt in Transgenic Potato Plants

Abstract: It has been established that drought-responsive element binding (DREB) proteins correspond to transcription factors which play important regulatory roles in plant response to abiotic and biotic stresses. In this study, a novel cDNA encoding DREB transcription factor, designated StDREB1, was isolated from potato (Solanum tuberosum L.). This protein was classified in the A-4 group of DREB subfamily based on multiple sequence alignments and phylogenetic characterization. Semi-quantitative RT-PCR showed that StDRE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 97 publications
(58 citation statements)
references
References 74 publications
1
57
0
Order By: Relevance
“…We have previously shown that overexpression of StDREB1 in transgenic potato plants increases the accumulation of the proline osmoprotectant by activating expression of d1-pyrroline-5-carboxylate synthetase (P5CS) gene (Bouaziz et al 2013). Similar results were also observed in transgenic alfalfa plants overexpressing GmDREB1 that showed an increase in the P5CS gene expression (Jin et al 2010).…”
Section: Overexpression Of Stdreb1 Increases the Expression Of Antioxsupporting
confidence: 57%
See 4 more Smart Citations
“…We have previously shown that overexpression of StDREB1 in transgenic potato plants increases the accumulation of the proline osmoprotectant by activating expression of d1-pyrroline-5-carboxylate synthetase (P5CS) gene (Bouaziz et al 2013). Similar results were also observed in transgenic alfalfa plants overexpressing GmDREB1 that showed an increase in the P5CS gene expression (Jin et al 2010).…”
Section: Overexpression Of Stdreb1 Increases the Expression Of Antioxsupporting
confidence: 57%
“…Our previous results suggested that the StDREB1 factor may belong to this group of transcription factors that activate the expression of genes harboring both the GCC box and DRE target sequences (Bouaziz et al 2013). To further confirm this hypothesis, a recombinant HisStDREB1 protein was overexpressed in E. coli.…”
Section: Stdreb1 Protein Binds To Both Dre and Gcc Elementsmentioning
confidence: 88%
See 3 more Smart Citations